The complete mitochondrial genome of Antarctic Phaeodactylum tricornutum ICE-H - Lina Liu; Yingying He; Kai Wang; Jinlai Miao; Zhou Zheng (Mitochondrial DNA. Part B. Resources, 2020)
In this study, the complete mitochondrial genome (mtDNA) of the Antarctic Phaeodactylum tricornutum ICE-H was sequenced using Illumina NovaSeq PE150. The circular mtDNA was 77055 bp in size and encodes 60 genes, contains 24 tRNA genes, 34 protein-coding genes, and 2 rRNA genes. The composition of A + T in ICE-H mtDNA was 65.34%. The phylogenetic relationship of 17 species of plant mitochondria were analyzed using the maximum likelihood method by the MEGA-X. Phaeodactylum tricornutum ICE-H was most closely related to Phaeodactylum tricornutum.